PENGARUH MODEL PENEMUAN TERBIMBING TERHADAP KETERAMPILAN PROSES SAINS DITINJAU DARI SIKAP ILMIAH PADA PEMBELAJARAN IPA - Virgi Puspita Dewi; Aris Doyan; Harry Soeprianto (Postgraduate, University of Mataram, 2017)
This study aims to determine: 1) the effect of learning model (guided discovery and conventional) against science process skills of students. (2) the effect of scientific attitudes (high and low) on learning science against science process skills of students. (3) the interaction effect between the learning model and scientific attitude on learning science against science process skills of students. The type of this research is a quasi experiment with a 2x2 factorial design. The population of this research is the students of SMPN 10 Mataram. The sample consisted of two classes defined by cluster random sampling. The instrument used consisted of a scientific attitude test a questionnaires and observation sheets science process skills. The data were analyzed by ANOVA, the analysis were performed using SPSS version 20 for windows with SPSS previously tested homogeneity and normality at significant level of 0.05. Based on the analysis we conclude : (1) there is no effect of using guided discovery model and conventional model against science process skills and critical thinking ability of students. (2) there is an effect of scientific attitude (high and low) on learning science against science process skills of students. (3) there is no effect of interaction between the learning model with a scientific attitude on learning science against science process skills of students.Keywords: Model of guided discovery, science process skills, scientific attitude